Modification of flax fibres by radiation induced emulsion graft copolymerization of glycidyl methacrylate - Moawia, R. M. (Elsevier Ltd, 2016)
Flax fibres were modified by radiation induced graft copolymerization of glycidyl methacrylate (GMA) by pre-irradiation method in an emulsion medium. The effect of reaction parameters on the degree of grafting (DOG) such as concentration of bleaching agent, absorbed dose, monomer concentration, temperature and reaction time were investigated. The DOG was found to be dependent on the investigated parameters. The incorporation of poly(GMA) grafts in the bleached flax fibres was confirmed by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The structural and mechanical changes were evaluated by X-ray diffraction (XRD) and mechanical tester, respectively. The results revealed that reacting bleached flax fibres irradiated with 20 kGy with 5% GMA emulsion containing 0.5% polyoxyethylene-sorbitan monolaurate (Tween 20) surfactant at 40. °C for 1 h led to a maximum DOG of 148%. The grafted fibres showed sufficient mechanical strength and hydrophobicity which make them promising precursors for development of adsorbents after appropriate chemical treatments.